Pedir ayuda a “Los otros” : algunas consideraciones en torno a la primera embajada bizantina en Córdoba (s. IX) - Diego Melo Carrasco (Estudios de Historia de España, 2016)
This article studies the motivations that, Teófilo, Bizantine Emperor, had for entering into contact with the Independent Emirate of Córdoba. From this perspective, some points are presented regarding the image of the Moslems, according to the Bizantine apologetics, with special mention of Constantine VII Porfirogénito’s work “De administando Imperio”. It is from this point that the analysis begins regarding the motives that “Basileus” had to send the first Byzantine Embassy to Córdoba, proving with this that where safeguarding the Empire was at stake, there would be no reasons to avoid contacts with those who might even be an enemy.